Unexpected synthesis, delayed emission and solid-state acidochromism of novel 2, 7-naphthyridine derivatives obtained from 2-(3, 5-diaryl-4H-pyran-4-ylidene)malononitrile. Issue 39 (27th September 2022) - Jiang, Yitian; Liu, Miaochang; Wang, Mengzhu; Lei, Yunxiang; Ding, Qiuping; Wu, Huayue; Huang, Xiaobo
Abstract : Two novel 2, 7-naphthyridines which are unexpectedly obtained from 2-(3, 5-diaryl-4 H -pyran-4-ylidene)malononitrile and benzylamine display phosphorescence, thermally activated delayed fluorescence, and high contrast solid-state acidochromism. Abstract : Two novel 2, 7-naphthyridine derivatives are unexpectedly synthesized by the reaction of 2-(3, 5-diaryl-4 H -pyran-4-ylidene)malononitrile and benzylamine, and are achieved through different ring-closing mechanisms. These two derivatives with twisted molecular conformations display phosphorescence, thermally activated delayed fluorescence, and high contrast solid-state acidochromism due to special chemical structures.